2021
DOI: 10.1177/0961000621996410
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the process of personal digital archiving through ubiquitous and desktop devices: A systematic review

Abstract: The purpose of this study is to explore Personal Digital Archiving, and its practices, reasons, and challenges in desktop and in ubiquitous environment such as desktop computers, laptops, mobile phones or smartphones, tablets, and cloud services. Moreover, it is also aimed to develop a model of Personal Digital Archiving process for desktop and ubiquitous devices. This study used Preferred Reporting Items for the Systematic Review and Meta-Analysis guidelines for searching and devising, and inclusion and exclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Although studies have been conducted on different aspects of PDA, such as PDA behaviour (Xiangjun, 2018), practice (Marčetić, 2015; Zhao et al , 2019), challenges (Ali and Warraich, 2022b; Sinn et al , 2017) and influencing factors (Sinn et al , 2017). But no comprehensive research has been carried out regarding the impact of mobile self-efficacy on PDA practices in terms of information backup, clearing and deleting.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although studies have been conducted on different aspects of PDA, such as PDA behaviour (Xiangjun, 2018), practice (Marčetić, 2015; Zhao et al , 2019), challenges (Ali and Warraich, 2022b; Sinn et al , 2017) and influencing factors (Sinn et al , 2017). But no comprehensive research has been carried out regarding the impact of mobile self-efficacy on PDA practices in terms of information backup, clearing and deleting.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review 2.1 Personal digital archiving PDA is a growing area of PIM activities and practices. Ali and Warraich (2022b) conducted a systematic review and identified 22 studies related to PDA practices, reasons and challenges within the context of PIM.…”
Section: Mobile Selfefficacy As Predictormentioning
confidence: 99%
See 3 more Smart Citations